A net present worth analysis of considered academic programs at a private, regional higher education institution - Doss, Daniel A.; Jones, Don Wayne; Sumrall, William; Henley, Russ; McElreath, David; Lackey, Hilliard; Gokaraju, Balakrishna (Journal of Interdisciplinary Studies in Education, 2015)
This paper examines the situation of a private, liberal arts college that sought toenhance its competitiveness by investigating the financial potential and viabilityof offering either a complete human resources degree program or a graduatecertificate with an emphasis area in human resources as a method of bolsteringits strategic position within its academic market. The net present worth (i.e., netpresent value) method was the analytical method of financial analysis. The netpresent worth outcomes indicated that the complete degree program was thepreferred alternative.